2017
DOI: 10.1155/2017/6762047
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of and Factors Associated with the Anterior Chamber Volume in Healthy Chinese Adults

Abstract: Purpose. To measure the anterior chamber volume (ACV) and determine factors associated with the ACV in healthy Chinese adults. Methods. In this cross-sectional study, we used swept-source optical coherence tomography (SS-OCT) to measure ACV and other anterior segment parameters. Factors associated with ACV were also determined. Results. A total of 313 healthy Chinese adults were enrolled. The anterior segment parameters, including ACV, could be measured by SS-OCT with excellent repeatability and reproducibilit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 28 publications
2
9
0
Order By: Relevance
“…However, our study showed a 40.2% decrease in ACV, even after LPI, indicating that the decrease in the ACD after ICL insertion plays a more dominant role in the change in ACV than does LPI. A study conducted on healthy Chinese adults reported that the ACV was correlated with most of the anterior segment parameters, especially ACD, which accounted for approximately 85% of the variation in the ACV [ 8 ], consistent with the findings in the current study.…”
Section: Discussionsupporting
confidence: 91%
“…However, our study showed a 40.2% decrease in ACV, even after LPI, indicating that the decrease in the ACD after ICL insertion plays a more dominant role in the change in ACV than does LPI. A study conducted on healthy Chinese adults reported that the ACV was correlated with most of the anterior segment parameters, especially ACD, which accounted for approximately 85% of the variation in the ACV [ 8 ], consistent with the findings in the current study.…”
Section: Discussionsupporting
confidence: 91%
“…Image tracking with averaging is a unique aspect of this swept-source AS-OCT as well. For sweptsource OCT, other anterior segment OCTs have been developed [ 11 17 ], but they lacked image tracking and averaging and could not visualize the entire lens thickness (from anterior to posterior pole). The importance of averaging is the main reason why posterior segment OCT is so widely used and clinically applicable [ 6 8 ].…”
Section: Discussionmentioning
confidence: 99%
“…Swept-source OCT (SS-OCT), using a ~1300 nm laser, improved on this with better speed and depth of penetration [ 4 ]. Multiple publications have described SS-OCT for imaging the cornea, anterior chamber, anterior chamber angle, and iris [ 11 17 ], although tracking capabilities and full lens thickness imaging could not be performed. Thus, SS-OCT has some inherent advantages for AS-OCT due to its speed and image coverage for large areas at a wavelength which provides more detailed information about ocular anatomy.…”
Section: Introductionmentioning
confidence: 99%
“…A carefully monitoring of anterior chamber angle and IOP is required in the early postoperative period. However, despite that the longer period results suggested a great stability of anterior chamber angle, regular visits are essential as the anterior chamber space decreases with age, especially after 40 years of age [ 24 ].…”
Section: Discussionmentioning
confidence: 99%